EDUKASI MENGENAI FAKTA DAN MITOS EPILEPSI DI POLI SARAF RUMAH SAKIT UNIVERSITAS MATARAM - Wardi, Baiq Prita Riantiani; Harahap, Herpan Syafii; Putri, Setyawati Asih; Suryani, Dini; Fitriantoro, Santo; Putri, Siti Noururrifqiyati Juna; Landapa, Raditya Rachman; Linggabudi, I Gusti Bagus Widiamtara; Maharani, Amelia Wahyu; Syifa, R.R Ditya Mutiara; Anugrah, M. Fardi; Shafa C, Cloresta; Ismaya, Ferium Trah (Jurnal Abdi Insani, 2025)
Epileptic seizures have a significant negative impact on the lives of patients, especially those who frequently experience relapses due to low medication adherence. Epilepsy patients often face stigma and social discrimination. Misunderstandings and negative societal attitudes, influenced by myths surrounding epilepsy, can prevent patients from seeking treatment and living confidently. This community service activity aimed to provide information and education about epilepsy, covering topics from its definition to an in-depth discussion of myths and facts about the disease. The ultimate goal was to enhance the knowledge of patients, their families, and visitors at the neurology outpatient clinic of Mataram University Hospital. The activity was conducted through interactive counseling sessions using PowerPoint presentations. Participants completed a pre-test before the counseling session, followed by a question-and-answer discussion after the material was delivered, and concluded with a post-test. A total of 56 participants attended. Both pre-test and post-test consisted of five questions addressing basic knowledge about the definition of epilepsy, myths and facts, and appropriate actions when encountering an epileptic seizure. The average pre-test score was 68.57, while the average post-test score increased to 76.44 after the educational session and discussion. Effective communication, education, and information dissemination proved to be key solutions for improving participants' knowledge. These efforts are expected to help epilepsy patients avoid stigma, gain full support from family and their surroundings, ensure optimal treatment outcomes, and enable patients to live confidently. Effective education and communication are critical in improving understanding of epilepsy, reducing stigma, and fostering social support for epilepsy patients.